Board-Level prototype validation: a Built-in controller and extended BS architecture - Gustavo Costa Alves (1999)
Prototype validation is becoming a major concern and hardship in modern electronic products design and development. Simulation, structural test, functional debug and timing debug are all constituting parts of the validation process, although very often they are addressed as independent and dissociated tasks. In this paper we describe an integrated approach to board-level prototype validation, based on a set of mandatory / optional BST instructions and a built-in controller for debug and test.